(untitled) (Journal of Human Sciences, 2021)
The study aims to identify the level of satisfaction with the academic specialization of the Summary This research aims to highlight the educational and hyman values in “Sura Yusuf peace beupon him”، to show the lessons and sermons in the Sura amd to explain their interpretation ،ln ordehaved for parents to benefit from them and learn how to manage situation s wisely and well behaved, the researcher used the inductive and analytical approach in interpreting the verses and deriving the connotaions from them. Main results: 1.Not to differentiate in the treatment between chidren . 2-Do not leave strangers inside the housses.3- pay attention to lying scour ge and check every command.4- The future of charity with charity.5-punishment for the type of work. 6-The bad f uture of the good .7- Refuge in Allah when advesity. 8- The need to consolidate educational values in school currcula.9- Research in other aspects of the Holy Quran.